The Quantification and chemical characterization of exopolysaccharides (EPS) produced by a strain of Penicillium sp. isolated from Antarctica (Revista Científica Ciencias Naturales y Ambientales, 2016)
The worldwide interest on exopolysaccharides (EPS) production has increased due to the versatility in its uses as biosurfactants, emulsifiers, and antibiotics among others. The aim of this work was to determine EPS production from a strain of Penicillium sp. isolated from Antarctica. The assay was performed under a factorial design on MEB and PDB culture media, those were evaluated under the following conditions: temperature 25°C and 30°C; pH: 6, 7, and 8; and a constant stirring at 130 rpm. The chemical composition of EPSs tested in the present study were carbohydrates, protein, acetyl residues, pyruvate residues and hexosamines. The best results were: proteins 9,984±1.5 μg/g in MEB, pH 8 and 25°C, acetyl residues 2742±1983 μg/g in PDB, pH 6 at 30°C, carbohydrates 2,5495±1.43 μg/g in PDB, pH 8 to 25°C, hexosamines 7.53±6.41 mg/g in PDB, pH 6 at 30°C and residues of pyruvate 4242±3087 μg/g in PDB, pH 8 at 25°C. The production of EPS depends on the parameters under which the fungus was submitted, among those, pH and temperature were the determining factors on the process. In addition, no proportional correlation between biomass production and EPS was determined.
Keywords: Acetyl residues; carbohydrates; exopolysaccharides; hexosamines; pyruvate; Penicillium sp.